IMPLEMENTASI SIMULASI MONTE CARLO PADA PENGADAAN BARANG TOKO “X” - Karmila, Sely (Jurnal Informatika dan Komputasi STMIK Indonesia Jakarta, 2013)
An information must have good quality and have to be belived the trueness, this was based that the information has some factor that effects the quality of the information itself, that is accuraccy, timing, relevancy, and the persentation. Because of that, the act of information was very important as a service provider for them who need information. Transaction process that happen in “X” store is a daily operational process, wich is a facts, if we analogy it with the meaning of a data, we can conclude that the daily operational process was data. We also can`t predict what kind of goods would sold in the next day, this makes each daily transaction events was a probabilistic models and it was random, doesn`t have a current pattern. In this case, the use of monte carlo methods in almira store system to do item selling simulation, was able to estimate how many stocks that must be availble in 1 day. So it can gives advantage to the manager to optimize their procurement processto keep the stokcs.